2020
DOI: 10.3390/en13092238
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Strengthen Heat Transfer Performance of PCM by Active Stirring

Abstract: Latent heat storage has higher energy density, but most phase change materials (PCMs) have low thermal conductivity. Current research focuses on conduction dominated heat transfer mechanism to increase the heat transfer performance. However, convection also has important effects on promoting PCM melting and solidification processes. Therefore, an active stirring method with conduction dominated heat transfer mechanism was studied. A shell storage with stirrer inside was constructed and tested. Paraffin was sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The shell‐and‐tube type of LHTES is the most oftenused configuration as of its benefits, such as simple design, low cost, low‐pressure drop, large heat transfer area, high discharge power, and high efficiency 49 . Furthermore, the PCM will be placed between the two tubes, which directly exchange heat between the heat transfer fluid (HTF) and the working fluid, as proposed by several researchers 50–52 . Aside from that, the industry uses shells and tubes 90% of the time.…”
Section: Methodsmentioning
confidence: 99%
“…The shell‐and‐tube type of LHTES is the most oftenused configuration as of its benefits, such as simple design, low cost, low‐pressure drop, large heat transfer area, high discharge power, and high efficiency 49 . Furthermore, the PCM will be placed between the two tubes, which directly exchange heat between the heat transfer fluid (HTF) and the working fluid, as proposed by several researchers 50–52 . Aside from that, the industry uses shells and tubes 90% of the time.…”
Section: Methodsmentioning
confidence: 99%
“…In the first ten minutes the temperature of the material was found to be 50 °C and it reached 41 °C at 1 hour; also it was observed that it was not possible to achieve the ambient temperature with the time interval of 1.4 hours, however, the corresponding temperature at 1.4 hours was noted to be 32 °C. This is due to less turbulent motion resulting in slow rapid cooling and lesser stirring rate, as well as less lack of turbulent layer behaviour [Zhang et al, 2020].…”
Section: Methods Of Discharging Processmentioning
confidence: 99%
“…Two options are based on the internal energy change. First, time constants based on the total internal energy are referred to as charging time (e.g., [89,93,117,124,[163][164][165]) and are defined by Equation 32. Second, time constants based on the latent heat (e.g., [46, 68, 69, 72, 77, 83, 87, 88, 90, 93, 96, 98, 99, 102, 104, 107-109, 113, 119, 120, 125, 129, 131-134, 136, 149, 165-170]) which are called melting/solidification time and are defined by Equation 33with 𝜆 ̅ the total liquid fraction.…”
Section: Time Based Indicatorsmentioning
confidence: 99%